The place of the sacred with regard to gadamer's ontology, of art - Hafız, Muharrem (Marmara Üniversitesi İlahiyat Fakültesi Dergisi, 2010)
The experience of art-work is, for Gadamer, related to ınıılı which goes beyand the metlıodological knowledge. Hence discovering of truth is possible through the antology of art, and the experience of art is an experience of truth that can be applied to the hermeneutic problem in its whole dimension. The work of art is, in this respect, the experience of truth as an 'event'. Opposing to the aesthetic differentiat'i on which abstracts the work of art from its possibilities of content (religious, moral, culrural), Gadamer tries to overcome this distinction of consciousness through the concept of game. The reason of Dasein's inner rensian towards the "unknown" is the fact of remaining of the sacred/infinite as non-understanding. Gadamer argues that the work of art transforms the tension into the relaxation by means of the ontological hermeneutics of it. Therefore, the distinction between sacred and profane is relative in Gadamer; and all the works of art have always sacred about it and the sacred speeches ro us via the work of art. In this article, it will be seen how Gadamer establishes this togethemess with regard to the antology of art.
Keywords: sacred, the work of art, experience, truth, hermeneutic, game, rransfom1ation in to structure, contemporaneity